Design and Initial Results of the Minneapolis Heart Institute TeleHeart Program. Issue 10 (October 2017) - Newell, Marc C.; Strauss, Craig E.; Freier, Toby; Abdelhadi, Raed; Chu, Matthew; Campbell, Alex R.; Eckman, Peter; Hurrell, David G.; Lesser, John R.; Lindgren-Clendenen, Deborah; Longe, Terrence F.; Miedema, Michael D.
Abstract : Supplemental Digital Content is available in the text.